Bank of Dave [videorecording (DVD)] - Foggin, Chris, 1985-; Ashworth, Piers; Fry, Joel; Dynevor, Phoebe, 1995-; Hartley, Jo, 1972- (Samuel Goldwyn Films, 2023)
Based on the true-life experiences of Dave Fishwick; 'Bank of Dave' tells the story of how a working-class Burnley man and self-made millionaire fought to set up a community Bank.